Perception and Diffusion of Photovoltaic Systems among Potential Adopters in Rural Communities in Mexico : Case Study in Chiquilistlan, Mexico - Cisneros Chavira, Pablo (My University, 2021)
This study identifies the current perceptions high school students between the ages of 15-18 in rural communities in México have of photovoltaic (PV) systems and suggests proper ways to diffuse them. The empirical data was gathered through questionnaire-type surveys and semi-structured interviews conducted among high school students in Chiquilistlán, México. PV systems exist and are readily available worldwide. However, the desired implementation levels have not yet been reached in developing countries such as México, where approximately 1.5 million people lack access to electricity. The most significant impact of PV systems ought to be seen in rural communities, which account for 23% of the Mexican population. Due to their low population density and remoteness, rural areas tend to have deficient infrastructure that impedes their inclusion in the national electricity grids. Therefore, the need to locally supply electricity arises, and PV systems become the means to close the existing energy gap in the country. Furthermore, considering the yearly rise of the median age in México, the population is getting older. Hence the importance of knowing how younger generations in rural communities perceive PV systems. From the reasons stated above, the following research question was derived: how are photovoltaic systems perceived among potential adopters in rural communities and how to diffuse them properly? In order to answer to this question, three objectives were considered: (1) to identify the core perceptions of PV systems among potential adopters in Chiquilistlán, México; (2) to understand the socio-demographic aspects of potential adopters and identify relationships with their perceptions; and (3) to propose appropriate diffusion processes suitable for rural communities. Results show a higher perception of relative advantage of PV systems, followed by observability, compatibility, and simplicity. The primary motivators of potential adopters to positively perceive PV systems were generation monitoring, solar power potential, and income monitoring. On the other hand, maintenance, installation costs, and access to providers were the main barriers to a positive perception. Additionally, it was found that the kind of stove present at their homes, having (or not) internet access every day, their overall acceptance (or rejection) of PV systems, and their environmental awareness scores had a significant impact on how they currently perceive PV systems. Given the previous finding and based on interviewees’ responses, three main ways to approach potential adopters are proposed: face-to-face, online discussion groups, and printed information. If successfully performed, the perception of PV systems in rural communities in México will positively increase, leading to broader implementation in the medium and long run. The exploratory nature of the study allowed the researcher to make recommendations for future studies. The previous will contribute to closing the existing research gap to a reasonable extent.
Keywords: Mexico; rural communities; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management